Survivor of Sexual Violence in Quranic Perspective: MubÄdalah Analysis toward Chapter Joseph in Tafsir al-Azhar - Muhammad Haris Fauzi; Yuyun Affandi; Arikhah Arikhah (Pusat Studi gender dan Anak (PSGA) Universitas Islam Negeri Walisongo Semarang, 2020)
This research aims to examine and understand cases of sexual violence that befell the Prophet Joseph that was recorded in the verses of the Quran. The Prophet Joseph as a survivor of sexual violence suffered from verbal sexual harassment, attempted rape compulsion, and victim-blaming. The data is obtained by library research and analyzed using the socio-historical approach and qirÄâ€™ah mubÄdalah to analyze the method. The research results indicate that men and women must create a safe space of sexual violence and avoid destructive actions. The Prophet Joseph's strategic move came out of the circle of sexual violence and became a survivor by implementing the unity of God's values in various conditions.